Genome-wide identification of U-box gene family and expression analysis in response to saline-alkali stress in foxtail millet (Setaria italica L. Beauv) - Zhou, Xiaoke; Li, Yun; Wang, Jian; Zhao, Yuxue; Wang, Huimin; Han, Yucui; Lin, Xiaohu (Frontiers in Genetics, 2024)
E3 ubiquitin ligases are central modifiers of plant signaling pathways that regulate protein function, localization, degradation, and other biological processes by linking ubiquitin to target proteins. E3 ubiquitin ligases include proteins with the U-box domain. However, there has been no report about the foxtail millet (Setaria italica L. Beauv) U-box gene family (SiPUB) to date. To explore the function of SiPUBs, this study performed genome-wide identification of SiPUBs and expression analysis of them in response to saline-alkali stress. A total of 70 SiPUBs were identified, which were unevenly distributed on eight chromosomes. Phylogenetic and conserved motif analysis demonstrated that SiPUBs could be clustered into six subfamilies (I-VI), and most SiPUBs were closely related to the homologues in rice. Twenty-eight types of cis-acting elements were identified in SiPUBs, most of which contained many light-responsive elements and plant hormone-responsive elements. Foxtail millet had 19, 78, 85, 18, and 89 collinear U-box gene pairs with Arabidopsis, rice, sorghum, tomato, and maize, respectively. Tissue specific expression analysis revealed great variations in SiPUB expression among different tissues, and most SiPUBs were relatively highly expressed in roots, indicating that SiPUBs may play important roles in root development or other growth and development processes of foxtail millet. Furthermore, the responses of 15 SiPUBs to saline-alkali stress were detected by qRT-PCR. The results showed that saline-alkali stress led to significantly differential expression of these 15 SiPUBs, and SiPUB20/48/70 may play important roles in the response mechanism against saline-alkali stress. Overall, this study provides important information for further exploration of the biological function of U-box genes.